V(2)O(5)/TiO(2) catalytic xerogels raman and EPR studies - Rodella, C. B.; Franco, RWA; Magon, C. J.; Donoso, J. P.; Nunes, LAO; Saeki, Margarida Juri [UNESP]; Aegerter, M. A.; Sargentelli, V; Florentino, A. O. (Springer, 2002)
Raman spectroscopy and Electron Paramagnetic Resonance (EPR) studies were performed on a series of V(2)O(5)/TiO(2) catalysts prepared by a modified sol-gel method in order to identify the vanadium species. Two species of surface vanadium were identified by Raman measurements, monomeric vanadyls and polymeric vanadates. Monomeric vanadyls are characterized by a narrow Raman band at 1030 cm(-1) and polymeric vanadates by two broad bands in the region from 900 to 960 cm(-1) and 770 to 850 cm(-1). The Raman spectra do not exhibit characteristic peaks of crystalline V(2)O(5). These results are in agreement with those of X-ray Diffractometry (XRD) and Fourier Transform Infrared (FT-IR) previously reported (C.B. Rodella et al., J. Sol-Gel Sci. Techn., submitted). At least three families of V(4+) ions were identified by EPR investigations. The analysis of the EPR spectra suggests that isolated V(4+) ions are located in sites with octahedral symmetry substituting for Ti(4+) ions in the rutile structure. Magnetically interacting V(4+) ions are also present as pairs or clusters giving rise to a broad and structureless EPR line. At higher concentration of V(2)O(5), a partial oxidation of V(4+) to V(5+) is apparent from the EPR results.
Keywords: catalyst; vanadium and titanium oxides; sol-gel; characterization